IMPLEMENTASI PENGGUNAAN HAK INISIATIF UNTUK MENGHASILKAN PERATURAN DAERAH TENTANG PENGELOLAAN PEDAGANG KAKI LIMA YANG PARTISIPATIF DI KOTA PEKALONGAN - Djauhari Djauhari; Nurul Indrawati (Jurnal Pembaharuan Hukum, 2014)
The implementation of Act No.32 of 2004 about Local Government gives authority to each region to set up their households through the economic empowerment. One of the local economic development that significantly in contact with the public is with the management of street vendors. Structuring and management of vendors ranging from the provision of public space that does not ignore the rights of other members of society to the preparation of strict regulations should be considered a comprehensive solution including through the use of the right of initiative by members of the the Regional Representatives Council Pekalongan, so it can be known implementations use rights initiative of Parliament as well as the extent of public participation in the legislative drafting process. The method used in this study is a socio-juridical, namely to conduct a review of the legal aspects to know the rules that apply specifically related links use the right of initiative with community participation. Legislative function Legislative Council Pekalongan implementation of the rights owned embodied in the form of local regulations that have been generated. Legislative drafting from the Regional Representatives Council embodies the aspirations of the people against the people's representatives.